Impact of Decorin on the Physical Function and Prognosis of Patients with Hepatocellular Carcinoma - Kawaguchi, Takumi (J Clin Med, 2020)
The outcome of patients with hepatocellular carcinoma (HCC) is still poor. Decorin is a small leucine-rich proteoglycan, which exerts antiproliferative and antiangiogenic properties in vitro. We aimed to investigate the associations of decorin with physical function and prognosis in patients with HCC. We enrolled 65 patients with HCC treated with transcatheter arterial chemoembolization (median age, 75 years; female/male, 25/40). Serum decorin levels were measured using enzyme-linked immunosorbent assays; patients were classified into the High or Low decorin groups by median levels. Associations of decorin with physical function and prognosis were evaluated by multivariate correlation and Cox regression analyses, respectively. Age and skeletal muscle indices were not significantly different between the High and Low decorin groups. In the High decorin group, the 6-min walking distance was significantly longer than the Low decorin group and was significantly correlated with serum decorin levels (r = 0.2927, p = 0.0353). In multivariate analysis, the High decorin group was independently associated with overall survival (hazard ratio 2.808, 95% confidence interval 1.016–8.018, p = 0.0498). In the High decorin group, overall survival rate was significantly higher than in the Low decorin group (median 732 days vs. 463 days, p = 0.010). In conclusion, decorin may be associated with physical function and prognosis in patients with HCC.